THE RELATIONSHIP BETWEEN HABITS OF BREAKFAST AND ACADEMIC ACHIEVEMENT OF 3rd, 4th, AND 5th GRADE STUDENTS AT SDN SELOTAPAK SUBDISTRICT OF TRAWAS MOJOKERTO REGENCY - indah kusmindarti; Enny Virda Yuniarti (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2017)
The habit of having breakfast for school-age children is very important, because their school activities need more energy and calories. Children who do not have breakfast are more prone to hypoglycemia (low blood glucose levels) resulting in dizziness, cold sweat and fainted, which will eventually disrupt their activities. Not having breakfast will lead to decreasing learning interest and the power of their bodies. Research type was analyzed case control. The population was all elementary school students of 3rd, 4th, and 5th grade at SDN Selotapak, Trawas District, Mojokerto Regency with a sample of 91 respondents by using total sampling method. Data collection technique was conducted by using interviews and observation. Interviews were conducted to obtain a more in-depth information about the variables researched. Data analysis was conducted by using cross tab test. The habit of breakfast is important for students to help them meet their energy needs. It will make them more excited and more involved in learning. Moreover, their concentration and memory will be increased, that the children will be more confident and their academic achievement will increase.